2015
DOI: 10.1128/jb.00437-15
|View full text |Cite
|
Sign up to set email alerts
|

Coordination of Synthesis and Assembly of a Modular Membrane-Associated [NiFe]-Hydrogenase Is Determined by Cleavage of the C-Terminal Peptide

Abstract: During biosynthesis of [NiFe]-hydrogenase 2 (Hyd-2) of Escherichia coli, a 15-amino-acid C-terminal peptide is cleaved from the catalytic large subunit precursor, pro-HybC. This peptide is removed only after NiFe(CN) 2 CO cofactor insertion by the Hyp accessory protein machinery has been completed, suggesting that it has a regulatory function during enzyme maturation. We show here that in hyp mutants that fail to synthesize and insert the NiFe cofactor, and therefore retain the peptide, the Tat (twin-arginine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(37 citation statements)
references
References 58 publications
(120 reference statements)
3
33
1
Order By: Relevance
“…Previous studies revealed that the genetic removal of the C‐terminal extension of the large subunit results in hydrogenase devoid of a functional NiFe active site (Massanz et al, 1997; Thomas et al, 2015). To test whether the absence of the C‐terminal extension of the membrane‐bound hydrogenase (MBH) of R. eutropha also leads to inactive protein, we deleted the sequence encoding the amino acid residues Val604‐Arg618 of the HoxG subunit.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies revealed that the genetic removal of the C‐terminal extension of the large subunit results in hydrogenase devoid of a functional NiFe active site (Massanz et al, 1997; Thomas et al, 2015). To test whether the absence of the C‐terminal extension of the membrane‐bound hydrogenase (MBH) of R. eutropha also leads to inactive protein, we deleted the sequence encoding the amino acid residues Val604‐Arg618 of the HoxG subunit.…”
Section: Resultsmentioning
confidence: 99%
“…They observed that the genetically processed large subunit of E. coli Hyd2 lacks the native NiFe cofactor but forms a complex with the small subunit. The resulting inactive Hyd2 was even accepted by the Tat translocation apparatus and appropriately inserted into the cytoplasmic membrane (Thomas et al, 2015). Therefore, we analyzed the catalytic activity and the cofactor content of the MBH proc purified from the membrane fraction of R. eutropha HP9 and compared the results with those of R. eutropha HP3, synthesizing native MBH.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the processed HycE model structure, this Arg537 is buried within the protein, indicating a possible structural rearrangement after the proteolytic processing, as has been proposed for Hyd-2 [7,39]. The C-terminal extension of HycE itself has a total of 30% basic amino acids and HycH is predicted to be relatively acidic, however, with low conservation of these residues; thus, it is unlikely that the C-terminal extension is the interaction interface with HycH.…”
Section: Discussionmentioning
confidence: 98%
“…The proteins we have chosen not to study, S. enterica HydD, HydE and HydI are respectively identified as: a maturation protease found in the operons of all [NiFe] MBH and comparable to the structurally characterized protein E. coli HybD [29,30]; a large subunit maturase similar to E. coli HypC, R. eutropha HoxL [31] and Rh. leguminosarum HupF [28], which have well characterised roles in enzyme assembly; and a HypA homolog [2], which is believed to be involved in the final step of incorporating nickel into the metallocentre [32].…”
Section: S Entericamentioning
confidence: 99%